Resistivity Recovery in Fe and FeCr alloys - Gómez-Ferrer, Begoña; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book covers the Resistivity Recovery (RR) technique, underlying its physical principles, performance and problematic. A concise review on the state of the art is provided, showing the advances in radiation modelling, linking both experimental and theoretical fields. The reader will find a data compilation and comparison of up-to-date results obtained from the European Fusion Development Agreement model alloys. .
Thermonuclear Fusion -- Resistivity and experimental techniques -- Experiments on Resistivity -- State of the art -- Resistivity recovery on Fe and on Fe-Cr alloys -- Outlook. .
Keywords: Metals; Condensed matter; Nuclear engineering; Metals and Alloys; Condensed Matter Physics; Nuclear Energy